Kewajiban Notaris Dalam Melaporkan Transaksi Wajib Pajak Kepada Direktorat Jenderal Pajak (DJP) - Tasya Febrinda Apriantour (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
Notaries play an important role in the tax system by being required to report Taxpayer (WP) transactions to the Directorate General of Taxes (DJP). This obligation is regulated in Law Number 28 of 2007 concerning Income Tax (UU PPh) and Minister of Finance Regulation Number 31/PMK.03/2016. The main objective of this reporting is to improve taxpayer compliance, the accuracy of tax data, and the effectiveness of DGT supervision. Notaries are required to report various types of transactions, such as buying and selling land, grants, inheritances, and the granting of power of attorney regarding land and buildings. Reporting is carried out through a Research Certificate (SKP) Format of Proof of Fulfillment of the Obligation to Deposit Income Tax (PPh) Specifically for Notaries/Land Deed Making Officials (PPAT), either online via e-SPT PPh or manually at the Tax Service Office (KPP). Notaries who do not comply may be subject to sanctions, such as written warnings, fines, and even revocation of permits. Implementing this reporting obligation has benefits for notaries, such as increasing credibility and professionalism, streamlining the process of obtaining business permits, and making it easier to make deeds. Factors that influence notary compliance in reporting taxpayer transactions include knowledge and understanding of regulations, awareness and commitment, ease of reporting system, effectiveness of law enforcement, socialization and education, as well as a culture of tax compliance. Efforts to increase notary compliance require synergy from various parties, including the DJP, notary professional organizations, and the government in creating a culture of high tax compliance.